Status of ganges dolphin, Platanista gangetica gangetica (Roxburgh, 1801) in the river Buriganga, Dhaka (Bangladesh Journal of Zoology, 2015)
Population abundance and density of the Ganges River Dolphin Platanista gangetica gangetica (Roxburgh, 1801) was studied in the Buriganga River from December 2012 to November 2013.The survey was conducted twice a month. The dolphins were counted directly and applied in transect length of 10.5 km within 15 km stretches of the river. A total of 34 sightings of dolphins were recorded both in individuals and groups. We encountered the dolphins at the rate of 0.48 dolphins per km in the Buriganga River. Highest best-high-low estimate of 12-14-10 individuals were recorded in November 2013. The mean density was 0.38 (SD ±0.37) dolphins/km² with the highest density of dolphin observed also in the month of November, which was 1.14 dolphin/km². Pollution and water traffic were observed to be the major threats to the dolphins.Bangladesh J. Zool. 43(1): 109-120, 2015